2022
DOI: 10.1155/2022/6705948
|View full text |Cite
|
Sign up to set email alerts
|

Certificateless Reliable and Privacy-Preserving Auditing of Group Shared Data for FOG-CPSs

Abstract: FOG-enabled cyber-physical systems (FOG-CPSs) open new security challenges as the local edge devices are easier to compromise than a traditional cloud server. Remote data integrity checking (RDIC) plays an important role in safeguarding against data corruption from a storage server. Certificateless cryptography (CLPKC)-based RDIC schemes do not suffer from the drawbacks of the public key infrastructure (PKI)-based RDIC protocols. Most of the CLPKC-based RDIC schemes proposed in the literature deal with persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 78 publications
(163 reference statements)
0
5
0
Order By: Relevance
“…A robust data auditing protocol should be capable of preventing collusion between the edge device and the data auditor on the challenge information. The work presented in [42] is the first to tackle various adversarial scenarios specific to shared group data auditing in FOG-CPS networks under a certificateless security model. It was revealed that the CLC-based group data auditing protocols [28], [30] were vulnerable to metadata forgery and public key replacement attacks, as demonstrated in [42].…”
Section: B Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…A robust data auditing protocol should be capable of preventing collusion between the edge device and the data auditor on the challenge information. The work presented in [42] is the first to tackle various adversarial scenarios specific to shared group data auditing in FOG-CPS networks under a certificateless security model. It was revealed that the CLC-based group data auditing protocols [28], [30] were vulnerable to metadata forgery and public key replacement attacks, as demonstrated in [42].…”
Section: B Related Workmentioning
confidence: 99%
“…The work presented in [42] is the first to tackle various adversarial scenarios specific to shared group data auditing in FOG-CPS networks under a certificateless security model. It was revealed that the CLC-based group data auditing protocols [28], [30] were vulnerable to metadata forgery and public key replacement attacks, as demonstrated in [42]. The schemes proposed in [40] and [41] also adopt a similar metadata generation mechanism as [28], and are therefore vulnerable to these attacks.…”
Section: B Related Workmentioning
confidence: 99%
See 3 more Smart Citations